Pengaruh Komunikasi, Lingkungan Kerja, dan Motivasi Terhadap Kinerja Karyawan di PT Great Giant Pineapple - Doni Junanto; Nova Mardiana (CV. Multi Kreasi Media, 2023)
This study aims to determine whether there is an influence of communication, work environment, and motivation on the performance of employees at PT Great Giant Pineapple. The data collection method in this study utilizes primary data. Data analysis involves multiple linear regression and t-tests, using IBM SPSS version 25 software. The sample size for this study consisted of 100 respondents from PT Great Giant Pineapple. The sampling technique employed probability sampling with a simple random sampling method. The results of this study support the proposed hypothesis, indicating that communication, work environment, and motivation have a positive and significant impact on the performance of PT Great Giant Pineapple employees. Suggestions for the company include enhancing upward and downward communication, such as providing information about tasks and organizational policies, as well as encouraging employees to communicate any work-related challenges to their superiors. Additionally, efforts should be made to improve the physical work environment, particularly in terms of maintaining optimal air temperature. Furthermore, employees should be encouraged to recognize the importance of planning their tasks independently, even in the absence of supervision.